2022
DOI: 10.1177/0310057x221105297
|View full text |Cite
|
Sign up to set email alerts
|

Oral midodrine does not expedite liberation from protracted vasopressor infusions: A case-control study

Abstract: Vasopressor dependence is a common problem affecting patients in the recovery phase of critical illness, often necessitating intensive care unit (ICU) admission and other interventions which carry associated risks. Midodrine is an orally administered vasopressor which is commonly used off-label to expedite weaning from vasopressor infusions and facilitate discharge from ICU. We performed a single-centre, case-control study to assess whether midodrine accelerated liberation from vasopressor infusions in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…We thank Professor Myles for his correspondence ‘What is a case-control study?’ published in this edition of Anaesthesia and Intensive Care which clarifies the classification of case-control and cohort studies, in response to our original manuscript. 1 We agree our study is more appropriately categorised as a cohort study and thank Professor Myles for his constructive feedback.…”
mentioning
confidence: 79%
“…We thank Professor Myles for his correspondence ‘What is a case-control study?’ published in this edition of Anaesthesia and Intensive Care which clarifies the classification of case-control and cohort studies, in response to our original manuscript. 1 We agree our study is more appropriately categorised as a cohort study and thank Professor Myles for his constructive feedback.…”
mentioning
confidence: 79%
“…Several studies have documented the widespread use of midodrine among critically ill hypotensive patients despite the controversy over its effectiveness and safety. 15-18 There are studies showing that midodrine is useful for patients in the ICU receiving intravenous vasopressor treatment to expedite their discharge from the hospital 15,16 due to its impact on reducing intravenous vasopressor duration and improving their weaning period and mortality. 19-23 However, other studies reported that using midodrine resulted in extreme adverse events of bradycardia 10,11 and is not associated with a significant decrease in either ICU or hospital LOS, mortality, or ICU readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…19-23 However, other studies reported that using midodrine resulted in extreme adverse events of bradycardia 10,11 and is not associated with a significant decrease in either ICU or hospital LOS, mortality, or ICU readmissions. 17,18 A recently published meta-analysis including 314 patients of four randomized controlled trials found no significant difference in the duration of vasopressor treatment between patients in the midodrine group versus the control groups. 24 It also found no difference between the two groups in the time to vasopressor stop, vasopressor restart, ICU LOS, and hospital LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the use of midodrine for hemodynamic support in the ICU (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The earliest of these involved retrospective exploratory cohort studies with inconsistent midodrine administration protocols, heterogeneous and poorly de ned patient populations, small sample sizes, and variable study outcomes (13)(14)(15).…”
mentioning
confidence: 99%